Development of an Anticipatory Action Plan for flood and landslide hazard in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Gnanatheepan, W. (International Water Management Institute, 2023)
Climate-related disasters, especially in vulnerable regions like Sri Lanka, necessitate proactive and anticipatory measures. In response, a detailed community risk assessment was conducted in Nuwara Eliya, Ambagamuwa Divisional Secretariat Division (DSD) to develop anticipatory action plans for floods and landslides. Focusing on vulnerable populations, including impoverished families, pregnant women, and elderly communities, the Anticipatory Action Protocols aim to empower communities and reduce potential hazards' impact. The objectives of developing Anticipatory Actions include community empowerment, hazard impact reduction, and the encouragement of innovative disaster preparedness approaches. The Community Risk Assessment (CRA) framework employs tools such as transect walks, seasonal calendars, venn diagrams, and hazard maps to comprehensively assess local vulnerabilities and capacities. This process ensures a participatory approach, fostering a nuanced understanding of the community's dynamics. Anticipatory Action Plans are highly tailored, utilizing the information gathered from the CRA to address specific risks effectively. The CRA serves as a systematic methodology for identifying, estimating, and ranking various risks, enhancing community awareness, prioritizing risks, and providing indicators for measuring changes in vulnerability over time. The Anticipatory Action Intervention involves proactive strategies within disaster risk management. Feasibility studies identify high-risk areas and beneficiaries, and trigger statements guide timely implementation. A district-level technical advisory committee reviews the Early Action protocol, ensuring accountability and inclusiveness. External stakeholders, including plantation companies, contribute resources crucial for effective implementation. Preparedness activities involve developing community-based early warning mechanisms, aligning them with national thresholds, establishing vigilant groups, and providing training. The readiness stage includes identifying suppliers, executing trigger monitoring, validating beneficiary lists, and coordinating with communities. Prioritized early actions encompass getting timely forecasts, implementing cash-for-work, disseminating messages, mobilizing trained volunteers, and activating on-site monitoring. Other components address shelter, housing, and settlements; restoring livelihoods; water, sanitation, and healthcare; and education, with each segment focusing on specific preparedness, readiness, and prioritized early actions. The partnership and coordination section emphasizes establishing technical working groups, training community volunteers, and coordinating with external agencies for effective disaster management.